Sejarah Ekonomi Hijau: Mengurai Asal-Usul Dan Perkembangan Pemikiran Ekologis Dalam Ekonomi - Salong, Amjad (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2024)
This study examines the history and development of ecological thinking in economics, known as the green economy. Starting with the classical concept of resource limitations by economists such as Thomas Malthus and John Stuart Mill, the research explores the evolution of thought emphasizing the balance between economic growth and environmental sustainability. The early 20th-century conservation movement and the 1972 report